Avoidant Coping and Diabetes-Related Distress: Pathways to Adolescents’ Type 1 Diabetes Outcomes - Iturralde, Esti (Health Psychol, 2016)
OBJECTIVE: Adolescents with Type 1 diabetes (T1D) are vulnerable to diabetes-related distress and often struggle to complete self-management tasks needed to maintain blood glucose values in target range. One way that youth with T1D handle problems is through avoidant coping. The current study examined cross-time associations between avoidant coping style and diabetes outcomes and tested the possible mediating role of diabetes-related distress. METHOD: Adolescents with T1D (N = 264) were assessed 4 times over 1 year to measure avoidant coping style, diabetes-related distress, adherence (on the basis of glucometer data and self-report), and glycemic control (hemoglobin A1c). Mediation and direct effects were tested across time using time-lagged autoregressive path models, making use of the repeated measurement of all constructs. RESULTS: The hypothesized mediation effect was found for all 3 diabetes outcomes. Higher levels of avoidant coping style were associated with greater diabetes-related distress at the subsequent time point, which was related in turn to fewer blood glucose checks, less frequent self-care behaviors, and poorer glycemic control (higher A1c) at the next assessment. CONCLUSIONS: In the context of diabetes, an avoidant coping style may contribute to greater diabetes-specific distress followed by deterioration in self-management and glycemic control over time. Maladaptive coping styles are modifiable factors that offer an entry point into intervention before further difficulties can take hold.